2019
DOI: 10.1002/cncr.32339
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of pembrolizumab and circulating biomarkers to predict anticancer response in advanced, unresectable hepatocellular carcinoma

Abstract: BACKGROUND: Checkpoint inhibitors have shown modest activity in patients with advanced hepatocellular carcinoma (HCC). Herein, the authors report a prospective single-institution clinical/translational phase 2 study of pembrolizumab in patients with advanced HCC and circulating biomarkers closely related to response. METHODS: Pembrolizumab was administered at a dose of 200 mg intravenously every 3 weeks among patients who may have developed disease progression while receiving, were intolerant of, or refused so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 26 publications
(58 reference statements)
4
108
1
Order By: Relevance
“…There is no robust data reporting the effect of PD-L1 tumor expression as a predictive marker of response to pembrolizumab. Data on PD-L1 tissue expression as a predictive tool with pembrolizumab was previously reported in a single center uncontrolled intervention study in 29 patients with advanced HCC who had developed disease progression or were intolerant to sorafenib [ 174 ]. In this study, serum pro and anti-inflammatory cytokines, as well as serum levels of PD-1 and PD-L1 and PD-L2, were measured at baseline.…”
Section: Serum and Tissue Biomarkers In Hcc For Response Assessmenmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no robust data reporting the effect of PD-L1 tumor expression as a predictive marker of response to pembrolizumab. Data on PD-L1 tissue expression as a predictive tool with pembrolizumab was previously reported in a single center uncontrolled intervention study in 29 patients with advanced HCC who had developed disease progression or were intolerant to sorafenib [ 174 ]. In this study, serum pro and anti-inflammatory cytokines, as well as serum levels of PD-1 and PD-L1 and PD-L2, were measured at baseline.…”
Section: Serum and Tissue Biomarkers In Hcc For Response Assessmenmentioning
confidence: 99%
“…In only 10 patients there was tumor tissue available and only 4 were positive to PD-L1 staining, showing higher levels of plasma INF-y or IL-10 but PD-L1 staining was not correlated with plasma PD-L1 concentration. Plasma tumor-growth factor β (TGF-β) levels were associated with overall survival [ 174 ].…”
Section: Serum and Tissue Biomarkers In Hcc For Response Assessmenmentioning
confidence: 99%
“…Thus, a fraction of PD-L1-negative HCC patients showed objective clinical responses, demonstrating no significant difference compared to PD-L1 positive patients. This was recently confirmed by a study where the response to anti-PD-1 did not correlate with PD-L1 tumor staining in advanced HCC [27]. However, archival tissue samples were used and the number of evaluable patients in this study was very limited ( n = 10).…”
Section: Predictive Biomarkers Of Response To Pd-1/pd-l1 Blockadementioning
confidence: 59%
“…Detection of activating mutation in CTNNB1 should also be informative to know immune cold phenotype and lack of response to ICIs in HCC [41]. On the other hand, Feun et al indicated that baseline plasma TGF-β level could be a predictive biomarker for the response to pembrolizumab [80], and clinical trials of combined blockade of PD-1/PD-L1 and TGF-β axis are ongoing (Table 3). Dong et al analyzed multiple tumors of the same patients for genetic structure, neoantigens, T cell receptor repertoires, and immune infiltrates, and found that only a few tumors were under the control of immunosurveillance and the majority carry a variety of immune escape mechanisms, even in a single case [81].…”
Section: Current Limitation Of Immune Checkpoint Inhibitors and Challmentioning
confidence: 99%